How to change everything : the young human's guide to protecting the planet and each other - Klein, Naomi, 1970-; Stefoff, Rebecca, 1951- (Atheneum Books for Young Readers, 2022)
Explains the current state of the climate to young readers. Draws on examples of change and protest from around the world, as well as young activists, to describe actionable steps to reverse or slow climate damage and achieve climate justice. Includes resources and black-and-white photographs.